Dynamic characterization of machining robot and stability analysis. Issue 1 (January 2016) - Mejri, Seifeddine; Gagnol, Vincent; Le, Thien-Phu; Sabourin, Laurent; Ray, Pascal; Paultre, Patrick
Abstract Machining robots have major advantages over cartesian machine tools because of their flexibility, their ability to reach inaccessible areas on a complex part, and their important workspace. However, their lack of rigidity and precision is still a limit for precision tasks. Innovations and design optimization of robotic structure, links, and power transmission allow robot manufacturers to propose business solutions for machining applications. Beyond accuracy problems, it is also necessary to quantify the vibration phenomena that may affect, as in machine tools, the quality of machined parts and the tools and spindle lifespan. These vibrations occurred at specific machining conditions depending on robot and spindle dynamic properties. The robot's posture evolved significantly in its workspace and induces dynamic's changes observed at the tool tip that in turn impact the stability of the machining process. The objective of this paper is to quantify the dynamic behavior's variation of an ABB IRB 6660 robot equipped with a high-speed machining (HSM) spindle in its workspace and analyze the consequences in terms of machining stability. Through an experimental modal characterization, significant variability of modal parameters is observed at the tool tip and impacts the stability of machining. The results show that an adjustment of the cutting conditions must accompany the change of robot posture during machining to ensure stability.